Глибока ванна – шлях до інтенсифікації процесів тепломасообміну і підвищення енергоефективності дугової сталеплавильної печі - Тімошенко, С.М.; Губинський, М.В. (Physico-technological Institute of Metals and Alloys, 2023)
Analysis of recent research and publications. The heat loss by radiation in the electric arc furnace (EAF) is largely due to the traditional ideas of technologists about the appropriateness of a shallow flat bath with a ratio of diameter to depth of 5.0– 5.5, in contrast to the "deep" bath in a converter with a ratio of diameter to depth close to 1. Numerical studies have shown the possibility of reducing radiation energy loss by 8.5–49 %, depending on the energy technology regime, by implementing a “deep” bath in the EAF. At the same time, the influence of the geometry of the steelmaking bath on the processes of heat and mass transfer in the workspace, which determine the duration of melting and, therefore, the energy efficiency of the EAF, remains poorly researched. Purpose and methodology. The work is devoted to study of influence of the EAF melting bath geometric parameters on heat and mass transfer in the volume of the steel and at the phase boundaries. Methodology consists in numerical modeling of heat and mass transfer processes based on the mathematical model of liquid metal circulation during pneumatic mixing. Findings and research implications. The concept of improving the energy efficiency of the EAF by intensifying heat and mass transfer processes through improving the geometry of the steelmaking bath has been developed. Practical implications. On the basis of developed circulation model of pneumatic mixing the bath, it was found that when the diameter to depth ratio of the steelmaking bath is reduced from the traditional 5–5.5 to optimal, for given energy-technological mode, values of 2.5-1.8 with a constant mass of heat, become possible: intensification of scrap melting in liquid bath by 13–25 %, dephosphorization of steel by 3–25 %, homogenization of the bath by 1.15–3 times, and a decrease in iron loss during evaporation in the arc zone by 10–12 %.